Perbedaan ukuran dan bentuk lengkung gigi antara laki-laki dan perempuan suku Bugis, Makassar, dan Toraja Difference of size and shape of dental arch between male and female of Buginese, Makassarese, and Toraja - Irene Edith Rieuwpassa; Syamsiar Toppo; Sri Dian Haerawati (Journal of Dentomaxillofacial Science, 2012)
Factors which influence the dental arch changes including genetic and environment. This study aims to determine thedifferences in size and shape of dental arch between men and women of Buginese, Makassarese and Torajanese. Thisstudy is an observational study, with a cross-sectional study design. The sampling method was purposive sampling, andnumber of samples were 90 samples obtained from 90 people with 30 people for each tribe, consist of 15 men and 15women, aged 18-25 years, with full dentition. Data were obtained through tcasting models of the maxillary andmandibular samples then were measured by using a ruler and caliper, then calculated using formula to determine,register, and analyze the size and shape of dental arch. Using multiple statistics, including t-test, ANOVA, chi-squaretest, and marginal of homogenity test there are significant differences regarding the size and shape of dental archbetween men and women of the Buginese, Makassarese, and Torajanese. There is only significant difference ofmaxillary dental arch for Buginese, Makassarese, and Torajanese